The determinants of economic growth in Malaysia / Mohamad Shahril Azrin Sapian - Sapian, Mohamad Shahril Azrin (2017)
Malaysia has showed a tremendous growth of export in the last 4 decades. It has influenced the increase in economic growth during the period. Undoubtedly, it has become a major contribution to national income. In order to maintain its economic growth, Malaysia has managed to maintain a positive trade balance, exporting more goods than it imports except in 1982, 1991 and 1994 — 1997. The aim of this study is to investigate the performance of economic growth in Malaysia since year 1981 until year 2016 and to determine the main factors of economic growth in Malaysia. The data is obtain from World Bank Indicator during 35 years period. The dependent variables for this study is Gross Domestic Product (GDP) is used to measure the performance of economic growth. The independent variables are government expenditure, population, exchange rate, foreign domestic investment and export. This paper using Econometric Views 9 (Eviews 9) to interpret the data by using several analysis tools which are Variance Inflations Factors (VIF) to check whether there are any correlation between each of the independent variable. Other than that, this paper also use the White Test, to determine the variance error term is consistent. The exchange rate have negative while foreign direct investment have positive relationship with gross domestic product.